(untitled) (Iranian Journal of Kidney Diseases, 2009)
Introduction. We assessed the costs of hospital admissions and length of hospital stay in kidney allograft recipients admitted to our center, in order to rank hospitalization causes in terms of costly and prolonged admissions, to bring to light the respective correlates of costly and prolonged admissions, and to investigate the relationship between costs and length of rehospitalizations. Materials and Methods. In a retrospective study at Baqyiatallah Hospital, in Tehran, records of 358 posttransplant hospitalizations were reviewed for the costs and duration of hospital stay. The causes of rehospitalizations, relative frequency of prolonged stays in costly rehospitalizations, and also relative frequency of costly admissions in short and prolonged stays were evaluated. Results. Among rehospitalizations, 83.3% of those due to cerebrovascular accident were costly and 51% of those with graft rejection resulted in prolonged hospital stays. Costly admissions had a high regularity in cases of patients older than 60 years, end-stage renal disease due to diabetes mellitus, graft loss, intensive care unit admission, and hospitalizations accompanied by in death. Prolonged stays were more common in those who were admitted to intensive care unit and those who ultimately died. The Costs showed a significant correlation with the length of rehospitalization (r = 0.626, P = .001). Conclusions. The strong correlation between the length of hospitalization and posttransplant hospitalization costs means that the former should be curtailed by focusing on such correlates of high-cost admissions as high age and diabetes mellitus as the cause of kidney failure.